Optimization of maize irrigation strategy in Xinjiang, China by AquaCrop based on a four-year study - Zhu, Hongyan; Zheng, Bingyan; Nie, Weibo; Fei, Liangjun; Shan, Yuyang; Li, Ge; Liang, Fei (Agricultural water management, 2024)
Global water scarcity has become a non-negligible problem that threatens the sustainable development of agriculture. In order to alleviate the contradiction between grain demand and water resource constraints, it is particularly important to explore appropriate irrigation strategy so as to synergistically increase grain yield and water use efficiency (WUE). The AquaCrop model were locally calibrated to simulate optimal irrigation amount for different hydrological years using a four-year field measurements (from 2017 to 2020) of maize with two irrigation levels (2400 m3/ha and 4800 m3/ha) in Shihezi, Xinjiang, China. On this basis, regulated deficit irrigation (RDI) strategies were optimized based on the variation of water consumption and soil water content (SWC) during the maize growth period. Results suggest that the optimal irrigation amount under static strategy (fixed proportion irrigation in growing season) in the wet, normal, and dry years was 4733 m3/ha, 5381 m3/ha, and 6090 m3/ha, respectively. In dynamic strategies, the optimized RDI4 (65% Ir (the amount of water required for each irrigation interval) at R2-R5 stage) and RDI5 strategy (85% Ir at V6-V12 stage and 85% Ir at R2-R5 stage) can save irrigation water while maintaining high yield. Under the premise of basically maintaining high yield (18Mg/ha), compared with each year's irrigation amount of 4800 m3/ha, the RDI4 strategy can reduce the irrigation amount by 4.33% in 2017; although the irrigation amount was slightly increased by 2.77% under the RDI5 strategy in 2018, the yield could be increased by 3.65%; in 2019, the RDI5 strategy can save 49.44% of irrigation water, and the RDI4 strategy will save 24.13% of irrigation water in 2020. From this study, it is recommended that a single irrigation amount of 65% Ir in R2 to R5 stages of maize growth or 85% Ir in V6 to V12 stages and 85% Ir in R2 to R5 stages can save irrigation water while maintaining high yield (18 Mg/ha). •The AquaCrop model was locally calibrated based on a four-year field study.•The optimal static irrigation strategy in wet, normal, and dry years was given.•Slight water deficit should be applied in initial growth stage of maize.•Higher water deficit can be adjusted in the later growth stage of maize.•Soil moisture cannot be deficient in seedling, tasseling and silking stage of maize.